PENGEMBANGAN BUSANA PENGANTIN BANYUWANGI DENGAN MOTIF GAJAH OLING - Ardiningrum Putri Artanti; Inty Nahari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to describe the process, describe the results, and describe the presentation of the creation of Banyuwangi wedding attire featuring the Gajah Oling motif. The background of this research is the challenge of preserving cultural identity amidst globalization and fast fashion, with more than 40% of intangible cultural heritage threatened with extinction (UNESCO). Millennials tend to prioritize digitalization over the revitalization of traditions, including the syncretic wedding traditions of the Osing community in Banyuwangi, which adopt elements from royal, Hindu, Islamic, and multi-ethnic sources. Gajah Oling Batik, a distinctive coastal batik, possesses deeply philosophical motifs (Gajah Oling ornaments, dilem leaves, maggar flowers, jasmine, reversed bamboo shoots) that symbolize good fortune and spiritual strength. However, its usage has declined by up to 30% over five years due to a lack of varied designs, uncomfortable materials, and minimal modern adaptation. Previous studies (Ratnawati, 2010; Rosayyida et al., 2023) focused on philosophical meaning and multiculturalism but have not yet integrated this motif into modern wedding attire using a sustainable design approach.